Spectrum of Vulvar Lesions in an Obstetrics and Gynecology Outpatient Clinic - Ozhan Ozdemir; Mustafa Erkan Sari; Funda Arpaci Ertugrul; Ertugrul Sen; Bunyamin Ugur Ilgin; Cemal Atalay (Medicine Science, 2015)
Wide range lesions may occur in the vulvar region. The aim of the present study is to have an insight into the diverse morphologic spectrum of vulvar lesions. Total of 263 patients with primary vulvar complaints seen in Ankara Numune Training and Research Hospital Gynecology and Obstetrics Outpatient Clinic were recruited into study. The present retrospective study was carried out by compiling the data from archival records from January 2010 to May 2014. The vulvar biopsies specimens were studied for histomorphological features. The lesions were categorized as non-neoplastic, neoplastic and inconclusive; neoplastic ones were further divided into benign, malignant and premalignant.The age of the women ranged from 11 to 85 years (mean 46.27±14.32) with the maximum number of patients between 41 to 50 years of age. Most common clinical presentation was itching (126 cases; 47.9%). The commonest site of vulvar lesions was labia majora (145 cases, 55.1%). Non neoplastic lesions were more common (n = 172; 65.4%) than the neoplastic lesions (n =91; 34.6%). There were 81 (30.8%) benign lesions while 10 cases (3,8%) were malignant or premalignant ones. Amongst the non-neoplastic lesions, the most common histopathologic diagnosis was of lichen sclerosus et atrophicus (46 cases; 17,5%). Early recognition of vulvar lesions and a prompt biopsy diagnosis for all lesions with suspicious changes is of great significance. [Med-Science 2015; 4(1.000): 1876-84]